Turkish pediatric atypical hemolytic uremic syndrome registry: initial analysis of 146 patients. Issue 1 (December 2017) - Besbas, Nesrin; Gulhan, Bora; Soylemezoglu, Oguz; Ozcakar, Z.; Korkmaz, Emine; Hayran, Mutlu; Ozaltin, Fatih
Abstract Background Atypical hemolytic uremic syndrome (aHUS) is a devastating disease with significant morbidity and mortality. Its genetic heterogeneity impacts its clinical presentation, progress, and outcome, and there is no consensus on its clinical management. Methods To identify the characteristics of aHUS in Turkish children, an industry-independent registry was established for data collection that includes both retrospective and prospective patients. Results In total, 146 patients (62 boys, 84 girls) were enrolled; 53 patients (36.3%) were less than 2 years old at initial presentation. Among the 42 patients (37.1%) whose mutation screening was complete forCFH, CFI, MCP, CFB, C3, DGKE, andCHFR5 genes, underlying genetic abnormalities were uncovered in 34 patients (80.9%). Sixty-one patients (41.7%) had extrarenal involvement. During the acute stage, 33 patients (22.6%) received plasma therapy alone, among them 17 patients (51.5%) required dialysis, and 4 patients (12.1%) were still on dialysis at the time of discharge. In total, 103 patients (70.5%) received eculizumab therapy, 16 of whom (15.5%) received eculizumab as a first-line therapy. Plasma therapy was administered to 84.5% of the patients prior to eculizumab. In this group, renal replacement therapy was administered to 80 patients (77.7%) during the acute period. A total of 3 patients died during the acute stage. A total of 101 patients (77.7%) had a glomerular filtration rate >90 mL/min/1.73 m2 at the 2-year follow-up. Conclusions The Turkish aHUS registry will increase our knowledge of patients with aHUS who have different genetic backgrounds and will enable evaluation of the different treatment options and outcomes.